Radiographic Evaluation of Permanent Canine Development Based on Nollas Stage of Tooth Development In 6–8-Year-Old Male Children - KARPAGAM, G. NITHYA; T, DR. BHAGYA LAKSHMI; PRABU, DR. DINESH (The journal of contemporary issues in business and government, 2021)
The aim of this study is to radiographically evaluate the permanent canine development based on nollas stage of tooth development in 6 to 8 year old male children. A total of about 400 orthopantamograhic (OPG) images were collected from the database record of the dental institution between June 2019-March 2020. Of these 51 OPGs were selected based on the age group between 6-8 years old male children. Dental age of developing permanent canine was calculated based on the nollas method. After data collection statistical analysis was done in SPSS software. Among the study population 47.1% were 8 years old, 45.10% were 7 years old and 7.84% were 6 years old. Considering the distribution of teeth assessed 31.37% were 13, 31.37% were 43, 21.57% were 33 and 15.69% were 23. Within the limitations of the study it was concluded that, majority of the canine teeth assessed among 6 to 8 years old children had canine almost completed (Stage 5) or crown completed (Stage 6) according to Nollas stage of tooth development. All the children in the age group of 6 years had 2/3rd crown completed in canine (Stage 4). Majority of the children in the age group of 7 years and 8 years had ‘crown almost completed’ (Stage 5).